Climate adaptation finance and investment in California - Keenan, Jesse M., 1979- (Routledge focus on environment and sustainability., 2019)
"This book serves as a guide for local governments and private enterprises as they navigate the unchartered waters of investing in climate change adaptation and resilience. This book serves not only as a resource guide for identifying potential funding sources but also as a roadmap for asset management and public finance processes. It highlights practical synergies between funding mechanisms, as well as the conflicts that may arise between varying interests and strategies. While the main focus of this work is on the State of California, this book offers broader insights for how states, local governments and private enterprises can take those critical first steps in investing in society's collective adaptation to climate change"--